Technology of Qualitative Analysis to Understand Community Political Behaviors in Regional Head Election in Wates District, Kediri, Indonesia - Suwarno, I Gusti Gede Heru Marwanto, Basrowi (International Journal of Advanced Science and Technology, 2020)
This study aimed to determine and analyse the political behaviour of The Village Chief from Wates sub-district, Kediri, East Java, Indonesia in the regional head election 2015 and factors influenced to the political behaviour which formed. This study approach used the qualitative experimental. The selection of the informant was purposively selected and used as the primary instrumentation. The data collection was conducted based on deep interview technique and participative observation; Data analysis technology used is to use the ATLAS.ti software. This software is useful in helping the process of analyzing data types of qualitative research grounded theory, in processing data each data is given a coding making it easier for researchers later to recall the data as discussion material in his research. The result showed that the political behaviour of Village Chief included to harmonisation behaviour. This behaviour can minimalise the tension, conflict, and create the tranquillity and live harmonised with the society during the regional head election process.Keywords: consolidation, democratisation, harmonisation politic, the regional head election.